Degradable polyolefin functional master batch and preparation method thereof

A degradable polyolefin masterbatch with photosensitizers and fillers accelerates the degradation of polyolefin plastics, maintaining mechanical integrity and ensuring rapid environmental breakdown.

CN119119632APending Publication Date: 2024-12-13HUNAN ZHIZHEN BIOTECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311053573.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Polyolefin plastics, such as polyethylene and polypropylene, are difficult to degrade and have slow degradation rates, especially in complex environments, leading to environmental pollution.

Method used

A degradable polyolefin functional masterbatch comprising polyolefin resin, modified filler, photosensitizer, dispersant, antioxidant, and coupling agent, which accelerates photodegradation through a combination of photosensitizers and degradable fillers, ensuring rapid degradation in various climatic conditions.

Benefits of technology

The masterbatch maintains mechanical properties while enabling rapid degradation of polyolefin plastics into small molecular compounds, facilitating environmental breakdown by soil microorganisms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of polyolefin master batches, in particular to a degradable polyolefin functional master batch and a preparation method thereof.The degradable polyolefin functional master batch is prepared from, by weight, 50-80 parts of polyolefin resin, 10-50 parts of modified filler, 3-5 parts of photosensitizer, 0.5-1.2 parts of dispersing agent, 0.2-2 parts of antioxidant, 1-2 parts of plasticizer and 0.2-1 part of coupling agent. The invention aims to enable the polyolefin functional master batch to have good mechanical properties, different products can be prepared, and the products prepared from the polyolefin functional master batch are degradable and can be quickly degraded in various different climatic environments, so that the pollution of plastics to the environment is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyolefin masterbatches, and in particular to a degradable polyolefin functional masterbatch and a preparation method thereof. Background Art

[0002] While people are studying the recycling technology of waste plastics, degradable plastics have also become a research hotspot around the world. Degradable plastics can be roughly divided into photodegradable plastics and biodegradable plastics. Photodegradable plastics are made by adding photosensitizers to resins. The photosensitizer particles in the resin can strongly absorb ultraviolet rays in the sun. The energy absorbed and released is enough to cut the molecular chains of polymers, resulting in photodegradation reactions. Products made from such degradable resins degrade under natural conditions to achieve natural reduction. Biodegradable plastics are made by adding biodegradable substances to degradable resins, so that biodegradable plastics can be completely degraded in the natural environment.

[0003] At present, polyolefins are mainly composed of polyethylene and polypropylene, both of which are difficult to degrade plastics. Although the degradation of polyolefin plastics can be accelerated by adding photosensitizers or degradable fillers, the degradation rate of polyolefin plastics is still relatively slow when they are naturally degraded by soil. Especially in some complex environments, the degradation of polyolefin resins will be further restricted due to environmental factors. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a degradable polyolefin functional masterbatch and a preparation method thereof, so that the polyolefin functional masterbatch has good mechanical properties and can be used to prepare different products. The products prepared from the polyolefin functional masterbatch are degradable and can be rapidly degraded in various climatic environments, thereby reducing the pollution of plastics to the environment.

[0005] The present invention solves the above technical problems by the following technical means:

[0006] A degradable polyolefin functional masterbatch comprises the following raw materials in parts by weight: 50-80 parts of polyolefin resin, 10-50 parts of modified filler, 3-5 parts of photosensitizer, 0.5-1.2 parts of dispersant, 0.2-2 parts of antioxidant, 1-2 parts of plasticizer and 0.2-1 parts of coupling agent.

[0007] Preferably, the polyolefin functional masterbatch comprises the following raw materials in parts by weight: 65 parts of polyolefin resin, 40 parts of modified filler, 4 parts of photosensitizer, 0.8 parts of dispersant, 0.45 parts of antioxidant, 1.5 parts of plasticizer and 0.6 parts of coupling agent.

[0008] Preferably, the polyolefin resin is one or more of low-density polyethylene, high-density polyethylene, polypropylene, and poly-1-butene.

[0009] Preferably, the photosensitizer is one or more of a transition metal salt of N,N-dialkyldithiocarbamic acid, a transition metal salt of salicylic acid, iron thiocarbamate, iron dimethyldithiocarbamate, iron stearate, iron laurate, ferrocene, iron acetylacetonate, acetophenone, hexachloroacetone, tetramethyl-4,4-diaminoketone, and an ethylene / carbon monoxide copolymer.

[0010] Photosensitizers are also called photodegradants, photolyzers or photodegradation catalysts. Photodegradation is a degradation reaction of polymer materials by free radicals under sunlight. In order to accelerate the photodegradation reaction, photodegradants are added. Commonly used photodegradants are organic compounds containing double bonds and transition metal elements. The degradation principle is that a photochemical reaction occurs under light to produce free radical compounds, which then transfer the active hydrogen on the polymer molecular chain, causing the polymer molecular chain to break, thereby achieving polymer degradation.

[0011] Further preferably, the photosensitizer is a copolymer of ethylene / carbon monoxide, which is used in a resin material, can come into contact with food, is photodegradable, has low pollution, and can also promote the degradation of other resin materials.

[0012] Preferably, the dispersant is a mixture of stearamide and higher alcohols, the antioxidant is a mixture of hindered phenol and phosphite, the plasticizer is tributyl citrate, and the coupling agent is one or more of a titanate coupling agent, a silane coupling agent, and an aluminate coupling agent.

[0013] More preferably, the hindered phenol antioxidant is one of antioxidant 1010, antioxidant 1098, and antioxidant 1076, the phosphite antioxidant is antioxidant 168, specifically antioxidant 1010 and antioxidant 168, and the coupling agent is a silane coupling agent.

[0014] Preferably, the preparation of the modified filler comprises the following steps:

[0015] S1 Pretreatment of montmorillonite: Soak the montmorillonite in deionized water for 1-3 hours, stir, add adsorbent, continue stirring for 3-5 hours, remove the adsorbent, filter, and dry to obtain purified montmorillonite;

[0016] Preparation of S2 composite montmorillonite: placing the montmorillonite treated in step S1 in a lauryl glucoside solution, stirring for 2-5 hours in a water bath, adding nano sodium sulfate and titanate coupling agent after the stirring, and continuing to stir for 1-2 hours. After the reaction is completed, filtering, drying, placing in a planetary ball mill, and ball milling to obtain nano composite montmorillonite;

[0017] Preparation of S3 modified filler: Mix the composite montmorillonite treated in step S2 with polylactic acid and stir for 1-2 hours. Add silane coupling agent during stirring. After stirring, place in a grinder and grind at 60-70°C for 2-4 hours. After grinding, a modified filler is obtained. Store the modified filler in dry conditions.

[0018] Montmorillonite is a layered mineral composed of extremely fine particles of hydrous aluminum silicate, with a large specific surface area, containing water and some exchange cations between the crystal structure layers, with a high ion exchange capacity and a high water absorption and expansion capacity. The impurities of montmorillonite are removed by adsorption and purification. Montmorillonite is activated by lauryl glucoside solution to enhance the adsorption and ion exchange capacity of montmorillonite, nano sodium sulfate is mixed with montmorillonite, and nano sodium sulfate is cross-linked to the montmorillonite lamellar structure by titanate coupling agent to further enhance the hygroscopic performance of montmorillonite, and at the same time, the cations between the montmorillonite layers are exchanged to enhance its heat resistance and processing performance.

[0019] Polylactic acid is a completely degradable biodegradable material with good mechanical properties, physical properties, thermal stability, processing properties and compatibility. Polylactic acid begins to glass transition at 60-65°C. By cross-linking the polylactic acid at 60-70°C and coating it on the composite montmorillonite, the polylactic acid is crystallized on the composite montmorillonite, making the modified filler degradable and at the same time enhancing the mechanical properties, physical properties and processing properties of the modified filler.

[0020] Preferably, in step S1, the adsorbent is one or more of corn cob fragments, coarse bran, soybean powder, and rice husk.

[0021] Impurities in montmorillonite are removed through adsorption by natural adsorbents, and these natural adsorbents will not affect the montmorillonite itself, making them easy to remove.

[0022] The present application also discloses a method for preparing a degradable polyolefin functional masterbatch, and the method for preparing the polyolefin functional masterbatch is as follows:

[0023] Place polyethylene and polypropylene resin in a high-speed mixer and stir at 80-100°C for 10-20 minutes, add modified filler, dispersant and silane coupling agent and continue stirring for 15-30 minutes, add poly 1-butene resin and continue stirring at 120-140°C for 5-10 minutes, add photosensitizer, plasticizer and antioxidant and continue stirring for 5-10 minutes. After stirring, transfer to a screw extruder, set the main engine temperature to 160-180°C, the mold temperature to 170-190°C, the head temperature to 190-200°C, extrude, cool and pelletize to obtain a polyolefin functional masterbatch.

[0024] By selecting polyolefin resin and adding it at different times, the functional properties of the entire polyolefin plastic are adjusted, so that the polyolefin plastic has good low-temperature resistance, impact strength, flexural resistance, and stress cracking resistance. By adding modified fillers, dispersants, and silane coupling agents, the modified fillers are evenly distributed in polyethylene, polypropylene, and poly-1-butene. Then, a photosensitizer is added so that the photosensitizer can contact the modified filler. By adjusting the dosage of the photosensitizer and the modified filler, the degradation induction time and brittle change period of the entire polyolefin are regulated, so that the products prepared from the polyolefin masterbatch can be used normally and can also be quickly degraded after use and discarded to avoid causing environmental pollution.

[0025] Preferably, the mass ratio of polyethylene, polypropylene and poly-1-butene is (1-2.5):(1-4)(0.5-1.2).

[0026] By adjusting the mass ratio of polyethylene, polypropylene and poly-1-butene, the basic properties of polyolefin plastics can be adjusted, so that the basic properties of different products can be adjusted according to different products.

[0027] The present application adopting the above scheme has the following beneficial effects:

[0028] The present application uses polyolefin resin as a matrix, and composites degradable fillers and photosensitizers, so that the products prepared by polyolefin masterbatch can not only ensure the mechanical properties and physical properties of the products, but also make the products degradable in different climatic environments after being discarded. For example, in areas with long sunshine, the molecular chains can be broken by the photosensitizer first, so that the macromolecular compounds are degraded into small molecular compounds, so that the small molecular compounds can come into contact with the soil. After the soil comes into contact with the degradable filler, the composite montmorillonite absorbs moisture while the polylactic acid is completely degraded, so that the microorganisms, bacteria, etc. in the soil fully degrade the small molecular substances, thereby rapidly degrading; when in areas with short sunshine, the polylactic acid is first degraded to form different depressions and holes on the polyolefin plastic, and the composite montmorillonite absorbs moisture at the same time, which is suitable for the survival of microorganisms, bacteria, etc. in the environment, thereby making the polyolefin plastic degradable, and then combined with the photosensitizer, the polyolefin plastic is further degraded, and the degradation rate is accelerated. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention:

[0030] Example 1, Preparation of polyolefin functional masterbatch

[0031] Preparation of modified fillers

[0032] S1 Pretreatment of montmorillonite: 10 parts by mass of montmorillonite was soaked in deionized water for 1 hour, stirred, and 3 parts by mass of a mixture of corncob fragments and coarse bran was added, and the stirring was continued for 3 hours. After the stirring was completed, the corncob fragments and coarse bran were removed, filtered, and dried at 50° C. for 12 hours to obtain purified montmorillonite;

[0033] Preparation of S2 composite montmorillonite: 10 parts by mass of the montmorillonite treated in step S1 is placed in 20 parts by mass of lauryl glucoside solution, and stirred for 2 hours in a water bath at 40-60°C. After the stirring is completed, 4.5 parts by mass of nano sodium sulfate and 0.5 parts by mass of titanate coupling agent are added, and the stirring is continued for 1 hour. After the reaction is completed, the mixture is filtered and dried at 80°C for 4 hours. The dried composite montmorillonite is placed in a planetary ball mill and ball-milled to obtain nano-composite montmorillonite. The particle size of the nano-composite montmorillonite is 33 nm as measured by a nano-particle size measuring instrument.

[0034] Preparation of S3 modified filler: 10 parts by mass of the composite montmorillonite treated in step S2 are mixed with 12 parts by mass of polylactic acid and stirred for 1 hour. During the stirring process, 1 part by mass of silane coupling agent is added. After stirring, the mixture is placed in a grinder and ground at 60°C for 2 hours. After grinding, a modified filler is obtained and the modified filler is stored in dry conditions.

[0035] Preparation of polyolefin functional masterbatch

[0036] 10 parts by mass of low-density polyethylene and 50 parts by mass of polypropylene resin are placed in a high-speed mixer and stirred at 80° C. for 20 minutes, 20 parts by mass of modified filler, 0.5 parts by mass of a mixture of stearic acid amide and higher alcohol and 0.2 parts by mass of a silane coupling agent are added and stirred for 15 minutes, 12 parts by mass of poly-1-butene resin are added and stirred for 10 minutes at 120° C., 3 parts by mass of an ethylene / carbon monoxide copolymer, 1 part by mass of tributyl citrate and 0.2 parts by mass of a mixture of antioxidant 1010 and antioxidant 168 are added and stirred for 10 minutes, after stirring, the mixture is transferred to a screw extruder, the main engine temperature is set to 160-180° C., the mold temperature is set to 170-190° C., the head temperature is set to 190-200° C., extrusion molding, cooling, and pelletizing are performed to obtain a polyolefin functional masterbatch.

[0037] Example 2, Preparation of polyolefin functional masterbatch

[0038] Preparation of modified fillers

[0039] S1 Pretreatment of montmorillonite: 20 parts by weight of montmorillonite was soaked in deionized water for 2 hours, stirred, and 7 parts by weight of a mixture of corncob fragments and coarse bran was added, and the mixture was stirred for 4 hours. After the stirring was completed, the corncob fragments and coarse bran were removed, filtered, and dried at 60° C. for 10 hours to obtain purified montmorillonite;

[0040] Preparation of S2 composite montmorillonite: 20 parts by mass of the montmorillonite treated in step S1 is placed in 45 parts by mass of lauryl glucoside solution, and stirred for 3.5 hours in a water bath at 40-60°C. After the stirring is completed, 10 parts by mass of nano sodium sulfate and 1.2 parts by mass of titanate coupling agent are added, and the stirring is continued for 1.5 hours. After the reaction is completed, the mixture is filtered and dried at 80°C for 6 hours. The dried composite montmorillonite is placed in a planetary ball mill and ball-milled to obtain a nano-composite montmorillonite. The particle size of the nano-composite montmorillonite is 35 nm as measured by a nano-particle size measuring instrument;

[0041] Preparation of S3 modified filler: Mix 20 parts by mass of the composite montmorillonite treated in step S2 with 25 parts by mass of polylactic acid, and stir for 1.5 hours. Add 2 parts by mass of silane coupling agent during the stirring process. After stirring, place in a grinder and grind at 65°C for 3 hours. After grinding, a modified filler is obtained, and the modified filler is stored in dry conditions.

[0042] Preparation of polyolefin functional masterbatch

[0043] 20 parts by mass of low-density polyethylene and 40 parts by mass of polypropylene resin are placed in a high-speed mixer and stirred at 90° C. for 15 minutes, 40 parts by mass of modified filler, 0.8 parts by mass of a mixture of stearic acid amide and higher alcohol and 0.6 parts by mass of a silane coupling agent are added and stirred for 25 minutes, 10 parts by mass of poly-1-butene resin are added and stirred for 8 minutes at 130° C., 4 parts by mass of ethylene / carbon monoxide copolymer, 1.5 parts by mass of tributyl citrate and 0.45 parts by mass of a mixture of antioxidant 1010 and antioxidant 168 are added and stirred for 8 minutes, after stirring, the mixture is transferred to a screw extruder, the main engine temperature is set to 160-180° C., the mold temperature is set to 170-190° C., the head temperature is set to 190-200° C., extrusion molding, cooling, and pelletizing are performed to obtain a polyolefin functional masterbatch.

[0044] Example 3, Preparation of polyolefin functional masterbatch

[0045] Preparation of modified fillers

[0046] S1 Pretreatment of montmorillonite: 30 parts by weight of montmorillonite was soaked in deionized water for 3 hours, stirred, and 10 parts by weight of a mixture of corncob fragments and coarse bran was added, and the mixture was stirred for 5 hours. After the stirring was completed, the corncob fragments and coarse bran were removed, filtered, and dried at 70° C. for 8 hours to obtain purified montmorillonite;

[0047] Preparation of S2 composite montmorillonite: 30 parts by mass of the montmorillonite treated in step S1 is placed in 60 parts by mass of lauryl glucoside solution, and stirred for 5 hours in a water bath at 40-60°C. After the stirring is completed, 18 parts by mass of nano sodium sulfate and 2.5 parts by mass of titanate coupling agent are added, and the stirring is continued for 2 hours. After the reaction is completed, the mixture is filtered and dried at 80°C for 10 hours. The dried composite montmorillonite is placed in a planetary ball mill and ball-milled to obtain a nano-composite montmorillonite. The particle size of the nano-composite montmorillonite is 41 nm as measured by a nano-particle size measuring instrument;

[0048] Preparation of S3 modified filler: 30 parts by mass of the composite montmorillonite treated in step S2 is mixed with 36 parts by mass of polylactic acid and stirred for 2 hours. During the stirring process, 3.5 parts by mass of silane coupling agent is added. After stirring, the mixture is placed in a grinder and ground at 65°C for 4 hours. After grinding, a modified filler is obtained, and the modified filler is stored in dry conditions.

[0049] Preparation of polyolefin functional masterbatch

[0050] 25 parts by mass of low-density polyethylene and 30 parts by mass of polypropylene resin are placed in a high-speed mixer and stirred at 100° C. for 10 minutes, 50 parts by mass of modified filler, 1.2 parts by mass of a mixture of stearic acid amide and higher alcohol and 1 part by mass of a silane coupling agent are added and stirred for 30 minutes, 5 parts by mass of poly-1-butene resin are added and stirred for 5 minutes at 140° C., 5 parts by mass of an ethylene / carbon monoxide copolymer, 2 parts by mass of tributyl citrate and 1 part by mass of a mixture of antioxidant 1010 and antioxidant 168 are added and stirred for 5 minutes, after stirring, the mixture is transferred to a screw extruder, the main engine temperature is set to 160-180° C., the mold temperature is set to 170-190° C., the head temperature is set to 190-200° C., extrusion molding, cooling, and pelletizing are performed to obtain a polyolefin functional masterbatch.

[0051] Example 4 (Comparative Example 1), Preparation of Polyolefin Functional Masterbatch

[0052] In this embodiment, the modified filler is the modified filler prepared in Example 2.

[0053] 20 parts by mass of low-density polyethylene and 40 parts by mass of polypropylene resin are placed in a high-speed mixer and stirred at 90° C. for 15 minutes, 40 parts by mass of modified filler, 0.8 parts by mass of a mixture of stearamide and higher alcohol and 0.6 parts by mass of a silane coupling agent are added and stirred for 25 minutes, 10 parts by mass of poly-1-butene resin are added and stirred for 8 minutes at 130° C., 1.5 parts by mass of tributyl citrate and 0.45 parts by mass of a mixture of antioxidant 1010 and antioxidant 168 are added and stirred for 8 minutes, after stirring, the mixture is transferred to a screw extruder, the main engine temperature is set to 160-180° C., the mold temperature is set to 170-190° C., the head temperature is set to 190-200° C., extrusion molding, cooling, and pelletizing are performed to obtain a polyolefin functional masterbatch.

[0054] Example 5 (Comparative Example 2), Preparation of Polyolefin Functional Masterbatch

[0055] In this embodiment, montmorillonite is used as filler, and the particle size of montmorillonite is the same as that of the montmorillonite raw material used in Embodiments 1-3, both of which are 0.5-2.0 um.

[0056] 20 parts by mass of low-density polyethylene and 40 parts by mass of polypropylene resin are placed in a high-speed mixer and stirred at 90° C. for 15 minutes, 40 parts by mass of montmorillonite, 0.8 parts by mass of a mixture of stearic acid amide and a higher alcohol and 0.6 parts by mass of a silane coupling agent are added and stirred for 25 minutes, 10 parts by mass of poly-1-butene resin are added and stirred for 8 minutes at 130° C., 4 parts by mass of an ethylene / carbon monoxide copolymer, 1.5 parts by mass of tributyl citrate and 0.45 parts by mass of a mixture of antioxidant 1010 and antioxidant 168 are added and stirred for 8 minutes, after the stirring is completed, the mixture is transferred to a screw extruder, the main engine temperature is set to 160-180° C., the mold temperature is set to 170-190° C., the head temperature is set to 190-200° C., extrusion molding, cooling, and pelletizing are performed to obtain a polyolefin functional masterbatch.

[0057] Example 6 (Comparative Example 3), Preparation of Polyolefin Functional Masterbatch

[0058] In this embodiment, the modified filler is the modified filler prepared in Example 2.

[0059] 20 parts by mass of low-density polyethylene and 40 parts by mass of polypropylene resin are placed in a high-speed mixer and stirred at 90°C for 15 minutes, 40 parts by mass of modified filler, 0.8 parts by mass of a mixture of stearamide and higher alcohol and 0.6 parts by mass of a silane coupling agent are added and stirred for 25 minutes, 4 parts by mass of an ethylene / carbon monoxide copolymer, 1.5 parts by mass of tributyl citrate and 0.45 parts by mass of a mixture of antioxidant 1010 and antioxidant 168 are added and stirred for 8 minutes at a temperature of 130°C, after stirring, the mixture is transferred to a screw extruder, the main engine temperature is set to 160-180°C, the mold temperature is set to 170-190°C, the head temperature is set to 190-200°C, extrusion molding, cooling, and pelletizing are performed to obtain a polyolefin functional masterbatch.

[0060] The polyolefin functional masterbatch prepared in Examples 1-6 was prepared into a film, and the tensile strength, impact strength, stress cracking resistance, and degradation rate were tested respectively, wherein the tensile strength, impact strength, and stress cracking resistance were tested in parallel in 3 groups, and the average value was taken. The test results are shown in Tables 1 and 2:

[0061] Table 1 Table 2

[0062] project Degradation rate (30d) Degradation rate (60d) Degradation rate (90d) Example 1 28% 41.6% 61.9% Example 2 31.5% 43% 63.2% Example 3 27.8% 40.5% 59% Example 4 23.1% 31% 45.4% Example 5 24% 30.7% 44.3% Example 6 26.6% 40% 56.7%

[0063] It can be seen from the data in Table 1 and Table 2 that the polyolefin functional masterbatches prepared in Examples 1-6 have good elongation at break, tensile strength, impact strength and stress cracking resistance when prepared into films, among which the elongation at break, tensile strength, impact strength and stress cracking resistance of the film prepared in Example 2 are better than those of other examples.

[0064] It can be seen from the data of Examples 2 and 4 that the addition of photosensitizer has little effect on the mechanical properties and physical properties of the film, but the addition of photosensitizer can significantly promote the degradation rate of the film;

[0065] It can be seen from the data of Example 2 and Example 5 that the addition of modified filler can improve the mechanical properties and physical properties of the film compared with adding only montmorillonite filler;

[0066] It can be seen from the data of Example 2 and Example 6 that the polyolefin film to which poly-1-butene is added can improve the mechanical properties and physical properties of the polyolefin film compared with the polyolefin film without adding poly-1-butene.

[0067] It can be seen from the degradation rates in Examples 2 and 4 that the modified filler and the photosensitizer can synergistically enhance the degradation rate of the film;

[0068] It can be seen from the degradation rates in Example 2 and Example 5 that the degradation rate of the film when the photosensitizer and montmorillonite are added is lower than the degradation rate when the modified filler and the photosensitizer are added simultaneously, indicating that the modified filler can increase the degradation rate of the film.

[0069] The above is a detailed introduction to a degradable polyolefin functional masterbatch and a preparation method thereof provided by the present invention. The description of the specific embodiment is only used to help understand the method and the core idea of ​​the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0070] It should be noted that if no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.

[0071] The above examples are intended to provide a better understanding of the present invention, and are not intended to be limiting of the best implementation mode described herein, nor are they intended to limit the content and protection scope of the present invention. Any product identical or similar to the present invention that is derived by anyone under the inspiration of the present invention or by combining the present invention with features of other prior arts shall fall within the protection scope of the present invention.

Claims

1. A biodegradable polyolefin functional masterbatch, It is characterized in that The invention comprises the following raw materials in parts by weight: 50-80 parts of polyolefin resin, 10-50 parts of modified filler, 3-5 parts of photosensitizer, 0.5-1.2 parts of dispersant, 0.2-2 parts of antioxidant, 1-2 parts of plasticizer and 0.2-1 parts of coupling agent.

2. A degradable polyolefin functional masterbatch according to claim 1, It is characterized in that The invention comprises the following raw materials in parts by weight: 65 parts of polyolefin resin, 40 parts of modified filler, 4 parts of photosensitizer, 0.8 parts of dispersant, 0.45 parts of antioxidant, 1.5 parts of plasticizer and 0.6 parts of coupling agent.

3. A degradable polyolefin functional masterbatch according to claim 1 or 2, It is characterized in that The polyolefin resin is one or more of low-density polyethylene, high-density polyethylene, polypropylene, and poly-1-butene.

4. The degradable polyolefin functional masterbatch according to claim 1, It is characterized in that The photosensitizer is one or more of a transition metal salt of N,N-dialkyldithiocarbamic acid, a transition metal salt of salicylic acid, iron thiocarbamate, iron dimethyldithiocarbamate, iron stearate, iron laurate, ferrocene, iron acetylacetonate, acetophenone, hexachloroacetone, tetramethyl-4,4-diaminoketone, and a copolymer of carbon monoxide.

5. A degradable polyolefin functional masterbatch according to claim 1 or 4, It is characterized in that The dispersant is a mixture of stearamide and higher alcohols, the antioxidant is a mixture of hindered phenol and phosphite, the plasticizer is tributyl citrate, and the coupling agent is one or more of a titanate coupling agent, a silane coupling agent, and an aluminate coupling agent.

6. The degradable polyolefin functional masterbatch according to claim 1, It is characterized in that The preparation of the modified filler comprises the following steps: S1 Pretreatment of montmorillonite: Soak the montmorillonite in deionized water for 1-3 hours, stir, add adsorbent, continue stirring for 3-5 hours, remove the adsorbent, filter, and dry to obtain purified montmorillonite; Preparation of S2 composite montmorillonite: placing the montmorillonite treated in step S1 in a lauryl glucoside solution, stirring for 2-5 hours in a water bath, adding nano sodium sulfate and titanate coupling agent after the stirring, and continuing to stir for 1-2 hours. After the reaction is completed, filtering, drying, placing in a planetary ball mill, and ball milling to obtain nano composite montmorillonite; Preparation of S3 modified filler: Mix the composite montmorillonite treated in step S2 with polylactic acid and stir for 1-2 hours. Add silane coupling agent during stirring. After stirring, place in a grinder and grind at 60-70°C for 2-4 hours. After grinding, a modified filler is obtained. Store the modified filler in dry conditions.

7. The degradable polyolefin functional masterbatch according to claim 6, It is characterized in that In the step S1, the adsorbent is one or more of corn cob fragments, coarse bran, soybean powder, and rice husk.

8. A method for preparing the degradable polyolefin functional masterbatch according to any one of claims 1 to 7, It is characterized in that The preparation method of the polyolefin functional masterbatch is as follows: Place polyethylene and polypropylene resin in a high-speed mixer and stir at 80-100°C for 10-20 minutes, add modified filler, dispersant and silane coupling agent and continue stirring for 15-30 minutes, add poly 1-butene resin and continue stirring at 120-140°C for 5-10 minutes, add photosensitizer, plasticizer and antioxidant and continue stirring for 5-10 minutes. After stirring, transfer to a screw extruder, set the main engine temperature to 160-180°C, the mold temperature to 170-190°C, the head temperature to 190-200°C, extrude, cool and pelletize to obtain a polyolefin functional masterbatch.

9. The method for preparing a degradable polyolefin functional masterbatch according to claim 8, It is characterized in that The mass ratio of the polyethylene, polypropylene and poly-1-butene is (1-2.5):(1-4)(0.5-1.2).

Citation Information

Cited By

  • Anti-aging sheath material and outdoor charging pile cable

    CN119708745A